DAMPAK PENDIDIKAN HOLISTIK PADA PEMBENTUKAN KARAKTER DAN KECERDASAN MAJEMUK ANAK USIA PRASEKOLAH - Latifah, Melly; Hernawati, Neti (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Character-based holistic education is new perspective that starting to be realized will give impact not only to character building but also to others developmental tasks, especially in preschool children. This study aims to analyze the impact of character-based holistic education to their multiple intelligences which was held in the preschool education in North Aceh District, Nanggroe Aceh Darussalam Province. This research design is cross sectional study. This study population is preschool age children (5-7 years), consists of children that attended in Taman Bermain Anak Semai Benih Bangsa (TBASBB)- as a nonformal education- and Taman Kanak Kanak (TK) -as a formal education-, and who do not attended in TBA-SBB/TK. The total samples -and his/her family- were 208. The result of the research showed that character of TBA-SBB participants significantly better than control group, even with a group of formal education (TK). Participants of TBA-SBB had the highest multiple intelligences and significantly different in all aspects of multiple intelligences than the control group. Character and multiple intelligences of the TBA-SBB participants are strongly influenced by the implementation of holistic education in TBA-SBB. Therefore, children who attend school with a good holistic education implementation will have a higher character and multiple intelligences score.